(untitled) (Revista Iberoamericana de Bioética, 2021)
The support provided by families to members with intellectual disabilities takes on various forms, mainly with regard to personal care and helping them to take decisions throughout their lives. Faced with this need for collaboration, a question raised in several international documents has been whether this support might not become a replacement for autonomy, rather than a support. Here we propose the hypothesis that, in cases of significant cognitive impairment, there is an inevitable communion between wills. Rather than a substitution per se, it would then become an active support in vital life situations.